Direct synthesis of mesoporous siliceous phosphotungstic acid and its superior catalytic activity on the cyclohexylation of phenol - Ilbeygi, Hamid; Sawant, Dhanashri P.; Ruban, Sujanya M.; Reshma, Kokane S.; Umbarkar, Shubhangi B.; Halligudi, Shivappa B.; Vinu, Ajayan (Journal of Physical Chemistry C, 2021)
The synthesis of highly active and reusable mesoporous siliceous phosphotungstic acid materials (mPTA-Si) which are prepared through a simple self-assembly between phosphotungstic acid (PTA), the polymeric surfactant, and the silica precursor assisted by KCl for cyclohexylation of phenol is reported. The surface area and the acidity of these materials are tuned with a simple adjustment of PTA in the silica framework. The prepared samples exhibit mesoporous structure with a high surface area, but the structure is collapsed when the loading of PTA is high. It is established that the Keggin structure of PTA is retained on the final mPTA-Si. mPTA-Si with different loadings of PTA are employed as the catalysts for the cyclohexylation of phenol under liquid phase conditions. Among the catalysts studied, 10.0-mPTA-8.3Si calcined at 350 degrees C is found to be highly active, selective, and recyclable and offers 100% conversion of phenol with the highest selectivity for p-cyclohexylphenol (96.8%).